A Bibliometric Analysis of Social Justice Movements and Popular Culture Intersection on Social Media - Erwin Erwin; Bambang Eko Prayetno; Ilham Akbar Bunyamin (West Science Social and Humanities Studies, 2023)
Using a bibliometric analysis, this study conducts a thorough investigation of the relationship between social justice movements, popular culture, and social media. Utilizing citation analysis, co-authorship networks, keyword co-occurrence, and temporal trends analysis, the study draws from a wide spectrum of scholarly publications, including seminal texts and modern contributions. The complex relationships found in the literature are made easier to show with the help of the visualization application VOSviewer. The analysis identifies important research areas and highlights topics including the effects of youth internet use, the contribution of popular culture to activism, and social network dynamics. The intellectual landscape is also shaped by important works by writers like Tarrow, McPherson, and Collins. Along with highlighting justice, race, and gender, the study also uncovers rising themes like diversity and group action through term occurrences. All things considered, this bibliometric analysis offers a thorough grasp of the intellectual landscape, generating a nuanced knowledge of the complex convergence of social justice, popular culture, and social media and providing ideas for future research.